2016
DOI: 10.1002/pi.5254
|View full text |Cite
|
Sign up to set email alerts
|

Size‐controlled preparation of nanosoy for potential biomedical applications

Abstract: Soy protein isolate nanoparticles (nanosoy) have significant applications in drug delivery, wound care systems and tissue engineering. We report an optimum technique named nanoprecipitation which enabled one-step formation of near-monodisperse nanosoy based on solvent displacement. Excellent control over protein aggregation was achieved, producing nanoparticles in the size range of 5-15 nm. The effect of various process parameters such as temperature, solvent/non-solvent ratio, crosslinker content and type of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…From Figure , it can be observed that a remarkable control over nanoparticle size was achieved with variation in temperature, where 5–15 nm and 90–140 nm particles were obtained at 30 °C and 50 °C, respectively. Nanoparticles in the size range of 0.2–0.7 μm were obtained at 60 °C, and the unfolding of proteins was evident at temperatures over 60 °C . Thus, particle size and polydispersity index (PDI) were found to increase with an increase in temperature.…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…From Figure , it can be observed that a remarkable control over nanoparticle size was achieved with variation in temperature, where 5–15 nm and 90–140 nm particles were obtained at 30 °C and 50 °C, respectively. Nanoparticles in the size range of 0.2–0.7 μm were obtained at 60 °C, and the unfolding of proteins was evident at temperatures over 60 °C . Thus, particle size and polydispersity index (PDI) were found to increase with an increase in temperature.…”
Section: Resultsmentioning
confidence: 96%
“…As described in the experimental section, the size‐controlled preparation of NS was carried out using a nanoprecipitation technique. A detailed examination of the influence of temperature, solvent/nonsolvent ratio, type of surfactant, and glyoxal crosslinking on the size and size distribution of NS was performed in our earlier studies . Briefly, a reaction temperature of 30 °C and solvent/nonsolvent ratio of 1:30 were optimized for the preparation of NS that acted as nanofiller for the dextran matrix in the present work.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The release behavior of CP from the GTG‐LC nanogels was analyzed as per previous reports 22, 25 . Approximately 10 mg of CP‐loaded GTG‐LC nanogels was dispersed in 20 mL of PBS for monitoring the release behavior.…”
Section: Methodsmentioning
confidence: 99%
“…In vitro CP release study The release behavior of CP from the GTG-LC nanogels was analyzed as per previous reports. 22,25 Approximately 10 mg of CP-loaded GTG-LC nanogels was dispersed in 20 mL of PBS for monitoring the release behavior. Drug release from nanogels was observed at different pH (2.5 and 6.5) at 37 °C for 0.5-24 h. The absorption maxima of the supernatant containing released CP were measured at a wavelength of 270 nm using a Shimadzu UV-2450 spectrophotometer against PBS as blank.…”
Section: ×100mentioning
confidence: 99%